Effect of Guided Inquiry Learning Model on Students Creative Thinking Skills in the Classification of Living Things Material - Hanna Turena Saragih; Halim Simatupang; Muflihani Pohan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
21st-century skills include several important components, including creative thinking. One skill that needs to be developed through the learning process in schools is creative thinking, as it helps students find solutions to problems and independently construct conceptual understanding. This study aims to determine the effect of the guided inquiry learning model on students’ creative thinking ability in the topic of classification of living organisms. This research is a quantitative study using a quasi-experimental design with a nonequivalent control group. The study population consisted of all seventh-grade students at SMP Negeri 17 Medan. The research sample was selected using a cluster sampling technique and consisted of two classes: class VII-7, the experimental class taught using the guided inquiry learning model, and class VII-9, the control class taught using direct instruction. The research instrument used was a test of creative thinking ability. The data were analyzed by testing the hypothesis using an Independent Samples t-test and normalized gain (N-Gain) analysis. The study's results indicate that the guided inquiry learning model affects students’ creative thinking abilities. The experimental class obtained an average posttest score of 81.56 with an N-Gain value of 63.92, which falls into the quite effective category, while the control class obtained an average posttest score of 69.38 with an N-Gain value of 44.28, which falls into the quite effective category. These results indicate that students’ creative thinking ability, when taught using the guided inquiry learning model, is better than that of students taught using conventional learning methods.